Open access and the academy: an analysis of some salient copyright and related legal interfaces - Wilson, Kenneth (2019)
This thesis offers an holistic approach to Open Access from a legal perspective. It does so by examining a series of interfaces between Open Access, law (especially but not exclusively copyright law), legal concepts and the Academy.